2005
DOI: 10.1002/ps.1085
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal and fungicidal activity of new synthesized chitosan derivatives

Abstract: Chitosan, the N-deacetylated derivative of chitin, is a potential biopolysaccharide owing to its specific structure and properties. In this paper, we report on the synthesis of 24 new chitosan derivatives, N-alkyl chitosans (NAC) and N-benzyl chitosans (NBC), that are soluble in dilute aqueous acetic acid. The different derivatives were synthesized by reductive amination and analyzed by 1H NMR spectroscopy. A high degree of substitution (DS) was obtained with N-(butyl)chitosan (DS 0.36) at a 1:1 mole ratio for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(91 citation statements)
references
References 35 publications
3
86
2
Order By: Relevance
“…Previous studies on the biological activity of chitosan and its derivatives against S. littoralis reported that the unmodified chitosan showed low insecticidal activity against larvae of S. littoralis, but its chemical modification led to an increase in the activity Rabea et al 2005Rabea et al , 2006Badawy 2008). Bioassays with 17 derivatives of N-(alkyl) chitosans at a rate of 5 g/kg diet demonstrated that N- (propyl) chitosan, N-(undecanyl) chitosan and N-(3-phenylpropyl) chitosan strongly inhibited larval weight gain in S. littoralis, with respective reductions of 77 and 65% after 4 days of feeding (Rabea et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the biological activity of chitosan and its derivatives against S. littoralis reported that the unmodified chitosan showed low insecticidal activity against larvae of S. littoralis, but its chemical modification led to an increase in the activity Rabea et al 2005Rabea et al , 2006Badawy 2008). Bioassays with 17 derivatives of N-(alkyl) chitosans at a rate of 5 g/kg diet demonstrated that N- (propyl) chitosan, N-(undecanyl) chitosan and N-(3-phenylpropyl) chitosan strongly inhibited larval weight gain in S. littoralis, with respective reductions of 77 and 65% after 4 days of feeding (Rabea et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Low-molecular-weight chitosan (made from coarse ground crab, 89% degree of deacetylation) was supplied by Sigma-Aldrich Co. (St. Louis, USA). Eight chemically modified chitosan derivatives, listed below in Figure 1, were prepared and characterized as described by Rabea et al (2005). The compounds with the indicated functional groups and different substituents were the following: compound 1, N-(p-chlorobenzyl)chitosan, compound 2, N- (o-chlorobenzyl)chitosan, compound 3, N-(p-fluorobenzyl)-chitosan, compound 4, N-(o-fluorobenzyl) chitosan, compound 5, N-(o,p-dichlorobenzyl)chitosan, compound 6, N-(o,o-dichlorobenzyl)chitosan, compound 7, N-(o,o-difluorobenzyl)chitosan and compound 8, N-(o-chloro,o-fluorobenzyl …”
Section: Methodsmentioning
confidence: 99%
“…N-(o,o-dichlorobenzyl)-chitosan within a series of N-(benzyl)chitosan derivatives was the most active compound against b. cinerea with EC 50 of 520 mg/l (Rabea et al 2005). In addition, N- (o,p-diethoxybenzyl) (Rabea et al 2009).…”
Section: Antibacterial Activity Of Chitosan Compoundsmentioning
confidence: 98%
See 1 more Smart Citation
“…Chitosan has been found to show strong insecticidal activity in some plant pests [45]. Rabea et al [45] found that a chitin derivative (N-(2-chloro-6-fluorobenzyl-chitosan) caused 100% mortality of larvae of the cotton leafworm (Spodoptera littoralis) that consumed it when incorporated into an artificial diet at 5 g kg −1 .…”
Section: Effectiveness Of Chitin-based Treatments Against Insect Pestsmentioning
confidence: 99%